Long-distance transfer of plasmonic hot electrons across the Au–Pt porous interface for the hydrogen evolution reaction. Issue 9 (5th February 2021) - Xia, Chang; Gao, Peng Fei; He, Wei; Wang, Ye; Li, Chun Hong; Zou, Hong Yan; Li, Yuan Fang; Huang, Cheng Zhi
Abstract : The hot electrons transfer from Au nanosphere to Pt interfaces is directly imaged by plasmon resonance light scattering microscopy. Remarkably, the hot electrons could persistently transfer across porous Au-Pt interfaces longer than 20 nm. Abstract : Plasmonic photocatalysis on bimetallic heterostructures via plasmonic hot electrons (eph − ) has received significant attention owing to their ability to harvest solar energy and high catalytic activities, whereas the mechanism of the eph − transfer at the metal–metal interfaces is still not completely understood owing to the chemical interface damping. Here, the eph − transfer from Au nanospheres (Au NSs) to the Pt interface is directly imaged by plasmon resonance light scattering (PRLS) microscopy. Under the plasmonic resonance illumination (PRI), eph − generated from Au NSs reduced PtCl6 2− to Pt(0) atoms, which are deposited on the surface of Au NSs to form a porous Au@Pt porous core–shell nanostructure (Au@Pt NS), and thus eph − could persistently transfer across the Au–Pt interface longer than 20 nm to further improve hydrogen evolution reaction (HER), which is further confirmed by ultrafast transient absorption spectra and transient photocurrent responses. This study promotes the understanding of the distance of eph − transfer at metal–metal interfaces to improve the separation efficiency of hot carriers in plasmonic-enhanced applications.